Sexual Violence and Major Depression among Women: Evidence for Reciprocal Relationships. (December 2019) - Schnittker, Jason
Using two waves of the National Comorbidity Survey, this study examines the relationship between sexual violence and major depression among women, focusing on rape. It uncovers evidence for two-way relationships that, among other things, shed light on who is at risk of sexual assault. Although rape increases the risk of developing major depression in a prospective fashion, depressed women are also at a higher risk of being raped. These pathways inflate the unadjusted prospective relationship between rape and major depression, though they do not explain it altogether. Comparisons between disorders indicate that major depression plays as significant a role as alcohol abuse disorder, and that depressed women are not at a higher risk only because of associated alcohol consumption. This study encourages further research not only on the effects of sexual violence on depression but also the role of common psychiatric disorders in the stress generation process, including how perpetrators target victims.